Linguistic Features and English Interference on Bahasa Indonesia Usage among Indonesian TikTok Users - Yudistira, Renaldy Serby; Dallyono, Ruswan (NOBEL: Journal of Literature and Language Teaching, 2024)
The development of English in Indonesia has increased rapidly. Many people learn English both through formal and non-formal education. However, this widespread exposure has also resulted in language interference, particularly when engaging on social media. This interference poses a potential shift in the features of Bahasa Indonesia as the national language. To investigate this issue, this study is designed to explore linguistic features affected by language interference and factors contributing to such language interference on TikTok, specifically among Indonesian TikTok users. To employ a qualitative research approach, data were obtained from post and comment sections of Indonesian TikTok users. The data were analyzed using Chaer and Agustina’s (2004) theory, which divided language interference into four types: lexical, syntactical, morphological, and phonological. Based on that theory, this study reveals that four linguistic features experienced language interference on TikTok: lexical (63%), syntactical (10%), morphological (22%), and phonological (5%). This study indicates three factors causing language interference in Indonesian TikTok users: language similarity, language contact, and terms of technological development. This research highlights the linguistic phenomenon of social media discourse in Indonesia.